PECULIARITIES OF THE PNEUMOCOCCAL PNEUMONIAE IN CHILDREN - T. A. Daminov; L. N. Tuychiev; N. U. Tadjieva; O. V. Raimkulova (LLC "Diagnostics and Vaccines", 2015)
147 children with community-acquired pneumococcal pneumonia aged from 6 months to 14 years old were hospitalized in Children's Lung Disease Department of the Clinic of Tashkent Medical Academy and in City Clinical Children's Hospital of Tashkent. The analysis of their anamnesis, clinical and laboratory data, which characterized the main clinical symptoms of the disease, blood picture, chest X-ray at has been performed. The analysis showed the prevalence of lobar pneumonia with frequent right-hand lesion of lungs and in rare cases it was accompanied by bacterial destruction of lungs and purulent pleurisy which proceeded with complications. The Immunochromatography BinaxNOW test and latex agglutination test allow to identify a pneumococcal etiology of pneumonia at early stages of the illness. Antibacterial therapy at a pre-hospital stage reduces efficiency of various diagnostic methods in the hospitalized patients, which makes it more rational to use of the method at a pre-hospital stage at a wider scale.